Are human herpes viruses associated with autoimmune thyroid disease? - Noura AL-Zarzour; Fawza Monem (Journal of Infection in Developing Countries)
Introduction: Autoimmune diseases are complex diseases with genetic, endogenous and environmental etiologies. Viral infections have been postulated as one of the factors that may be the trigger of autoimmune diseases.